2020
DOI: 10.3892/ol.2020.12263
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of interleukin‑10 concentration in the cerebrospinal fluid of patients with primary central nervous system lymphoma

Abstract: The diagnostic and prognostic evaluation of primary central nervous system lymphoma (PCNSL) is challenging due to the lack of sensitive biomarkers. The present study aimed to evaluate the value of interleukin (IL)-10 in this context. Between October 2016 and December 2018, 91 patients with suspected intracranial neoplasms were recruited, and the concentrations of IL-10 or IL-6 in both the cerebrospinal fluid (CSF) and blood were measured and analyzed by the Kruskal-Wallis test. The correlation between CSF IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Inflammation-related markers can be detected in the cerebrospinal fluid, which may aid the diagnosis of CNS tumors. Elevated levels of inflammatory markers, such as interleukin-10 and soluble interleukin-receptor, were found in the cerebrospinal fluid of primary CNS lymphoma (Geng et al, 2021). Specific cerebrospinal fluid biomarkers could help avoid high-risk biopsy operations and unnecessary craniotomy, and even guide preoperative surgical planning.…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Inflammation-related markers can be detected in the cerebrospinal fluid, which may aid the diagnosis of CNS tumors. Elevated levels of inflammatory markers, such as interleukin-10 and soluble interleukin-receptor, were found in the cerebrospinal fluid of primary CNS lymphoma (Geng et al, 2021). Specific cerebrospinal fluid biomarkers could help avoid high-risk biopsy operations and unnecessary craniotomy, and even guide preoperative surgical planning.…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%
“…Although only CCND2 was statistically significant in the survival analysis for the three hub genes, it did not mean that the other genes were meaningless. For example, some scholars found that CSF (cerebrospinal fluid) IL‐10 levels could be a sensitive biomarker for differential diagnosis, detection of early recurrence, prognostic evaluation, and therapeutic strategy establishment in PCNSL (primary central nervous system lymphoma) cases 27 . What's more, it had been reported that IL‐10 could promote tumor progression by promoting NF‐κB‐mediated transcription 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, some scholars found that CSF (cerebrospinal fluid) IL‐10 levels could be a sensitive biomarker for differential diagnosis, detection of early recurrence, prognostic evaluation, and therapeutic strategy establishment in PCNSL (primary central nervous system lymphoma) cases. 27 What's more, it had been reported that IL‐10 could promote tumor progression by promoting NF‐κB‐mediated transcription. 28 CD44 is a transmembrane glycoprotein involved in B‐cell migration and activation, and it associates with the extracellular matrix changes that influence cell growth, survival, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This review provided researchers with a basis for future validation studies of these markers in order to translate these candidate markers into clinically relevant diagnostic biomarkers. CXCL13 and IL-10 were found to be excellent diagnostic markers of CNSL and PCNSL, respectively, demonstrating high sensitivities and specificities and their relevance for assessment for clinical use [173,174]. Another prospective study identified a proliferation inducing ligand (APRIL) alone, or in combination with B cell activation factor (BAFF) as reliable diagnostic biomarkers.…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%